PENGARUH LINGKUNGAN KERJA NON FISIK DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN PADA BPR NUSA BANDUNG - Ardany, Yasmin Tiara; Wijaya, Fanji (STIE Mahardhika, 2024)
The research aims to correlate enthusiasm in completing tasks with various aspects, emphasizing top management's role in formulating compensation policies to enhance overall company values. This study focuses on BPR Nusa Bandung, a financial service institution offering loans to its clients. Through a preliminary survey, observations revealed discomfort among employees, including instances of misappropriation of funds for personal gain. The study's objectives include understanding employee motivation, assessing the non-physical work environment, examining compensation structures, and investigating the combined influence of the non-physical work environment and compensation on employee motivation at BPR Nusa Bandung. Employing a quantitative approach, data was collected using questionnaires and direct observations from 45 employees through a census sampling method. The analysis indicated a significant impact of non-physical work environment and compensation on employee motivation, with a 51% influence collectively. The study contributes insights into the interplay of these factors within the context of BPR Nusa Bandung, emphasizing the importance of addressing the work environment's physical and non-physical aspects to enhance employee motivation.